Grammatical Structure and Semantic Role Alignment of Verbal Arguments in South Nias - Rahmat Gaho (CV Wahana Publikasi, 2026)
This study aims to investigate the grammatical form of verbs, the function of verbs and the role of arguments for verbs in South Nias Language. This research was conducted in Telukdalam District, South Nias Regency. The research method used is descriptive qualitative. The main data is utterance or oral spoken which is then transcribed into written data. The results of the analysis show that there are two forms of grammatical verbs in South Nias Language, namely basic verb (free morphem) and derivative verb. The basic form of South Nias language verbs consists of the root form and the bound root form. The productivity of transitive and intransitive verb formation is influenced by morphological processes such as prefixes, suffixes, reduplication processes. Several types of prefixes were found to function as markers such as the prefix a- which is attached to the basic form, and semantically forms a passive meaning. The prefixes fa-, fe-, f-, and fo- form causative verbs. In addition, the prefixes te- and to form a resultative verb. Likewise, several types of suffixes form causative verbs such as suffix -i, -ö, -fi, -ni, -si, -khi, -mi, -gö, -i’ö, -content and -ini. Then, the function of verb of South Nias Language can become the core of the imperative clause. In addition, according to the transitivity nature of South Nias Language verbs it can form intransitive clauses which generally have one argument, namely S which acts as an AGENT (actor) such as the words me’e ‘cry’, mosindro ‘stand’, miwo ‘crow’, döröfö ‘sleepy’.